1977
DOI: 10.1172/jci108665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypercapnia and inspiratory flow-resistive loading on respiratory activity in chronic airways obstruction.

Abstract: A B S T R A C T The respiratory responses to hypercapnia alone and to hypercapnia and flow-resistive loading during inspiration were studied in normal individuals and in eucapnic and hypercapnic patients with chronic airways obstruction. Responses were assessed in terms of minute ventilation and occlusion pressure (mouth pressure during airway occlusion 100 ms after the onset of inspiration).Ventilatory responses to CO2 (AV/APco2) were distinctly subnormal in both grouips of patients with airways obstruction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
4
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 25 publications
7
51
4
1
Order By: Relevance
“…Most investigators have reported that the slope of this response is depressed in hypercapnic patients [6], but some [18], like the present authors ( fig. 1), found slopes equivalent to those in normocapnic patients.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Most investigators have reported that the slope of this response is depressed in hypercapnic patients [6], but some [18], like the present authors ( fig. 1), found slopes equivalent to those in normocapnic patients.…”
Section: Discussionmentioning
confidence: 46%
“…An inability to maintain a normal respiratory motor response during an exacerbation of COPD could lead to critical hypoventilation, respiratory failure, and death. Unfortunately, investigations have yielded inconsistent results, with reports of increased [4], decreased [5,6], and equivalent [7,8] respiratory motor output in hypercapnic and normocapnic patients. These conflicting findings stem, in part, from limitations of techniques used to measure respiratory motor output, such as the diaphragmatic electromyogram and airway occlusion pressure [9].…”
mentioning
confidence: 99%
“…The sensitivity can be reduced by genetic condition, observed in about 10% of the population, 14 or, in some patients, it can be acquired by chronic diseases such as chronic obstructive pulmonary disease 15 or diabetes 16 -conditions that were not present in our patients with SCI. In critically ill patients, sensitivity to CO 2 may also be reduced because of sedatives and opioids 17 used during mechanical ventilation, and because of the metabolic alkalosis 18 frequently observed with the use of diuretics and corticosteroids.…”
Section: Discussionmentioning
confidence: 85%
“…Is after the onset of inspiration (P0O.). (Whitelaw, Derenne & MilicEmili, 1975;Derenne, Couture, Iscoe, Whitelaw & Milic-Emili, 1976;Altose, McCauley, Kelsen & Cherniack, 1977;Burki, Mitchell, Chaudhary & Zecbman, 1977; Gqlb, Klein, Schiffman, Lugliani & Aronstam, 1977;Lopata et al, 1977).…”
Section: Inputs To the Respiratory Centrementioning
confidence: 99%